Defining other lands - Depetris, Carolina (Projeto História : Revista do Programa de Estudos Pós-Graduados de História, 2016)
How do we know other Geographies? How do we define other lands? This article suggests some answers to this question by taking Patagonia as scenario starting with the arrival of Magellan in 1520 until mid nineteenth-century. In this process of building a geographic knowledge, I set out from the analysis of two legends: the Patagonian Giants and the City of Césares. Then, through a rhetorical analysis of some travel journals annotated in the eighteenth and nineteenth centuries, we shall see how these legends were replaced by a solid epistemological apparatus that clearly defines this geographic region and the way in wich this epistemology correlates a precise discursive expression.